1975
DOI: 10.1111/j.1399-3054.1975.tb03883.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Extracellular Enzymes from Aphanomyces astaci and Their Relevance in the Penetration Process of Crayfish Cuticle

Abstract: In culture filtrates from the crayfish plague parasite, Aphanomyces astaci, protease and a low level of hyaluronidase activity were found. The hyaluronidase activity was highest at pH 6.5 or above and at about 23X. The protease activity had a broad pH-optimum, between pH 7 and at least pH 10, and was partially denatured at 30°C. However, when incubated for 30 min with the substrate, casein, the activity increased logarithmically up to about 35-4O°C and had an apparent optimum at 45-50°C.The proteases from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In inoculated sugarbeet seedlings, the protease activities were detected prior to or concomitant with the onset of disease symptoms and the activities were capable of digesting protein extracted from sugarbeet hypocotyls. Also, Soederhaell and Unestam (1975) found protease activity in culture filtrates from the crayfish plague parasite, Aphanomyces astaci. In addition, Dieguez-Uribeondo and Cerenius (1988) reported that species of Aphanomyces that attack fish (e.g., A. invidans) and crayfish (e.g., A. astaci) have been shown to produce abundant extracellular protease.…”
Section: Discussionmentioning
confidence: 99%
“…In inoculated sugarbeet seedlings, the protease activities were detected prior to or concomitant with the onset of disease symptoms and the activities were capable of digesting protein extracted from sugarbeet hypocotyls. Also, Soederhaell and Unestam (1975) found protease activity in culture filtrates from the crayfish plague parasite, Aphanomyces astaci. In addition, Dieguez-Uribeondo and Cerenius (1988) reported that species of Aphanomyces that attack fish (e.g., A. invidans) and crayfish (e.g., A. astaci) have been shown to produce abundant extracellular protease.…”
Section: Discussionmentioning
confidence: 99%
“…Many marine bacterial, fungal and protozoan pathogens secrete proteases during in vitro culture, suggesting that protease release could be important in pathogenesis. Examples include the salmon pathogen Aeromonas salmonicida (Rockey et al 1988), the crayfish pathogen Aphanomyces astaci (Söderhäll & Unestam 1975), and the oyster parasite Perkinsus marinus . Uronema marinum, a histophagous parasitic ciliate of the olive flounder Paralichthys olivaceus, has also been reported to secrete proteases during in vitro culture Identification and partial characterisation of metalloproteases secreted by a Mesanophrys-like ciliate parasite of the Norway lobster Nephrops norvegicus (Lee et al 2003); in this case, secreted proteases may be directly responsible for many of the clinical symptoms associated with the disease, such as tissue necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal and oomycete pathogens on insects and crustaceans secrete several types of lytic enzymes, including lipases, proteases and chitinases (Unestam 1966, Söderhäll & Unestam 1975, Persson et al 1984, Samuels et al 1989, Clarkson & Charnley 1996, Dieguez-*Corresponding author. E-mail: lage.cerenius@ebc.uu.se Uribeondo & Cerenius 1998, Vilcinscas & Götz 1999.…”
Section: Introductionmentioning
confidence: 99%